2017
DOI: 10.1007/s11211-017-0294-1
|View full text |Cite
|
Sign up to set email alerts
|

Putting Ourselves in Another’s Skin: Using the Plasticity of Self-Perception to Enhance Empathy and Decrease Prejudice

Abstract: The self is one the most important concepts in social cognition and plays a crucial role in determining questions such as which social groups we view ourselves as belonging to and how we relate to others. In the past decade, the self has also become an important topic within cognitive neuroscience with an explosion in the number of studies seeking to understand how different aspects of the self are represented within the brain. In this paper, we first outline the recent research on the neurocognitive basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 234 publications
(230 reference statements)
1
27
1
1
Order By: Relevance
“…Participants were embodied in a gender-matched photorealistic virtual body of either an 80-year old (virtual aging condition) or a 25-year old (control condition). Consistent with the findings of Study 2, there was no significant These findings demonstrate the transformative potential of virtual embodiment experiences evidenced in other intergroup contexts (for reviews see 34,35). For example, previous research has shown that racial bias can be reduced by embodying White participants in a Black virtual body (36)(37)(38).…”
Section: Studysupporting
confidence: 80%
“…Participants were embodied in a gender-matched photorealistic virtual body of either an 80-year old (virtual aging condition) or a 25-year old (control condition). Consistent with the findings of Study 2, there was no significant These findings demonstrate the transformative potential of virtual embodiment experiences evidenced in other intergroup contexts (for reviews see 34,35). For example, previous research has shown that racial bias can be reduced by embodying White participants in a Black virtual body (36)(37)(38).…”
Section: Studysupporting
confidence: 80%
“…In analysing the relationships between the levels of self-concept and empathy in the schoolchildren studied, a positive and direct relationship between self-concept and cognitive empathy was found. This means that schoolchildren with better self-concept have greater empathic abilities in their cognitive dimension, so that they are more effective in communicating, tolerating others and maintaining social relationships; as well as they have better abilities to recognise and understand other people’s emotions and impressions [56].…”
Section: Discussionmentioning
confidence: 99%
“…This self-enhancement effect appears to depend on a fronto-parietal network integrating information from visual and somatic sensory regions (Cardini et al, 2011). Studies have also shown that VRT effects for other's faces are increased after synchronous visuo-tactile stimulation (Cardini et al, 2013;Fini et al, 2013), a manipulation that has been shown to enhance perceived similarity in both bodily (Tsakiris, 2008) and social (Farmer and Maister, 2017;Paladino et al, 2010) domains.…”
Section: Introductionmentioning
confidence: 95%